Comparative Evaluation of Three Preprocessing Methods for Extraction and Detection of Influenza A Virus Nucleic Acids from Sputum - Yu, Fei; Qiu, Ting; Zeng, Ying; Wang, Yiyin; Zheng, Shufa; Chen, Xiao; Chen, Yu (Frontiers in Medicine, 2018)
Viscous sputum specimens usually cannot undergo automated extraction, and thus, a pre-homogenization process is desirable prior to isolating nucleic acids for rRT-PCR. In this study, we compared three preprocessing methods (preprocessing with normal saline, dithiothreitol, and proteinase K) of sputum specimens on the extraction and detection of influenza A virus (IAV) nucleic acids. Based on the experimental results of 217 specimens, we found that dithiothreitol and proteinase K could be used to improve the homogenization effects of sputum and increase the positive rates by 5.53%-6.91% higher than that of the normal saline group. Comparison of 49 positive specimens in all of the three groups demonstrated that the Ct values of the dithiothreitol group and proteinase K group were significantly lower and their nucleic acid concentration and A260/A280 ratio within 1.8-2.0 were higher than those of the normal saline group. Thus, sputum homogenization before nucleic acid extraction is essential for the accurate diagnosis of IAV infection.